2003
DOI: 10.1002/cncr.11379
|View full text |Cite
|
Sign up to set email alerts
|

Hypersensitivity and idiosyncratic reactions to oxaliplatin

Abstract: BACKGROUND Oxaliplatin is a third‐generation platinum analog that is used to treat a variety of solid tumors, particularly colorectal carcinoma. Patients may develop hypersensitivity reactions, although this complication occurs infrequently. METHODS Three patients developed hypersensitivity reactions to oxaliplatin while undergoing treatment on a Phase I trial of oxaliplatin and capecitabine. An Entrez PUBMED search was performed to identify other cases. RESULTS Two patients experienced the abrupt onset of ery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
109
0
3

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(132 citation statements)
references
References 38 publications
4
109
0
3
Order By: Relevance
“…The prevalence of hypersensitivity reactions was 10.7%, and this prevalence was consistent with previous studies with rate of 3.6%-25% (Andre et al, 2004;Brandi et al, 2003;Gowda et al, 2004;Maindrault-Goebel et al, 2005;Siu et al, 2006;Thomas et al, 2003). Most common events were cutaneous symptoms including rash and/or urticaria, and most symptoms were not severe: these results were also similar to results of previous studies (Shao et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The prevalence of hypersensitivity reactions was 10.7%, and this prevalence was consistent with previous studies with rate of 3.6%-25% (Andre et al, 2004;Brandi et al, 2003;Gowda et al, 2004;Maindrault-Goebel et al, 2005;Siu et al, 2006;Thomas et al, 2003). Most common events were cutaneous symptoms including rash and/or urticaria, and most symptoms were not severe: these results were also similar to results of previous studies (Shao et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…Patients who received less than 20mg dose of dexamethasone also had more risk of oxaliplatin hypersensitivity with adjusting age, sex, purpose of chemotherapy and oxaliplatin infusion dose. It has been reported that prophylactic regimens with corticosteroids and antihistamines are successful although effective prophylactic regimen of dexamethasone has not been determined (Bhargava et al, 2004;Brandi et al, 2003;Gowda et al, 2004;Lim et al, 2004;Maindrault-Goebel et al, 2005;Thomas et al, 2003). In a recent study, it has been reported that high dose dexamethasone plus antihistamine prevented colorectal cancer patients treated with modified FOLFOX-6 from hypersensitivity reaction to oxaliplatin (Kidera et al, 2011).…”
Section: Risk Factors For Oxaliplatin Hypersensitivity Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Platinum-containing agents are associated with hypersensitivity reactions, which have been reported to occur in 10% to 27% of patients treated with cisplatin or carboplatin [6]. The incidence of hypersensitivity reactions increases with multiple courses of the drugs and generally occurs after four to six courses [6,7]. Symptoms of hypersensitivity reactions to platinum-containing agents, which usually occur within minutes of administration in patients with prior exposure, include facial edema, bronchospasm, hypotension, tachycardia, pruritis, and erythema [6].…”
Section: Hypersensitivity Reactionsmentioning
confidence: 99%
“…Incidence rate allergic reactions is 0.55% in patients of advanced colorectal carcinoma ,who had received oxaliplatin 2 hrs infusion in combination with 5FU/LV (Thomas et al, 2003).It is argued that Patients with severe allergic manifestations should not be rechallenged to oxaliplatin exposure even is if appropriate symptomatic management is given/planned (Polyzos et al, 2001), whereas other studies advocate that the re-challenge protocol is effective treatment opinion in patients implicated with hypersensitivity and treated with Oxaliplatin (Yanai et al, 2012). Cheng et al (2008), reported 25 (11 females and 14 males) cases of allergic reactions in a prospective study in patients receiving FOLFOX 4 for colorectal carcinoma.…”
Section: Introductionmentioning
confidence: 99%